QORAQALPOGʻISTONDA YANTOQ (ALHAGI) DORIVOR OʻSIMLIGI ZARARKUNANDALARI - Abdullayev, I.I.; Bekbergenova, Z.O.; Jangabaeva, A.S. (SCIENCE and SOCIETY, 2025)
The article provides information on the species composition of the pests of the alhagi medicinal plant, which grows naturally in the Republic of Karakalpakstan.
Keywords: medicinal plants; pests; insects